Reserve bank of India and Monetary management - Gupta, G.P. (Bombay, 1959)
MONETARY policy plays a crucial role in shaping the economic destiny of a nation. Money and credit influence the course and volume of economic behaviour to a greater degree, Booms and depressions are, in a way, connected with the imperfect working of monetary institutions. Development schemes and their success ful implementation depend upon the correct and balanced policies adopted by the central monetary authority in the country. But, in India, as in other under-developed countries, little interest was! evinced in the art of monetary management, except during the v past two decades when Central Banking was harnessed as a positive science of "monetary management" to meet the exigencies, of war and to reconstruct the war-torn economy in the post war period. More recently, greater importance has come to be attached to the central banks as a necessary "cog" in the machinery of economic planning. To quote Paul Einzig: "Economic planning is unthinkable without monetary management and monetary management is doomed to failure without economic planning."
Keywords: Economics